BUILDING TEAM PERFORMANCE THROUGH LEADER'S EMOTIONAL INTELLIGENCE: THE ROLE OF A POSITIVE WORK CLIMATE - Sucipto, Imam; Rohmatul Manan, Irma (Media Inovasi Pendidikan dan Publikasi, 2026)
Team performance is an important factor in determining the success of an organization, especially in the face of increasingly complex work environment dynamics. One of the factors that plays a role in improving team performance is the leader's emotional intelligence. Leaders with good emotional intelligence are able to understand, manage, and express emotions effectively, so as to create a positive work climate. This study aims to analyze the influence of leaders' emotional intelligence on team performance with a positive work climate as a mediating variable. This study uses a quantitative approach with a survey method of team members in Outomotive Industry at Jababeka. Data were collected through questionnaires and analyzed using the SEM-PLS method. The results of the study show that the emotional intelligence of leaders has a positive and significant effect on team performance. In addition, a positive work climate has been shown to play a role as a mediating variable that strengthens the relationship between the leader's emotional intelligence and team performance. These findings indicate that leaders who have high emotional intelligence are able to create a conducive work environment, thereby encouraging optimal improvement in team performance. This research is expected to make a theoretical contribution to the development of human resource management studies and become a practical reference for organizations in developing leadership competencies based on emotional intelligence.